Learning qur'anic arabic through interactive web-based software: a pragmatic approach in language for specific purpose - Abdullah, Matin Saad; Pathan, Al-Sakib Khan (© 2013 IEEE., 2016)
This conference paper was presented in the 5th International Conference on Information and Communication Technology for the Muslim World, ICT4M 2013 [© 2013 IEEE.] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICT4M.2013.6518895